Disparitas Antar Wilayah Dan Provinsi Di Indonesia Sebelum Dan Sesudah Otonomi Daerah - Yanuar (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2013)
Since the application of local autonomy in Indonesia in 2001, there have been more opportunities for the local governments to organize and manage their regions. It is meant to achieve regional development targets in improving the people's welfare and quality of life in accordance with each region and province in Indonesia before and after the application of local autonomy. It used the descriptive method with secondary data from 1991 up to 2010 and the Gini coefficient analysis. This survey has concluded that the application of local autonomy has remained high, both among the regional and provincial levels. During the period of conducting this research, the local autonomy has not significantly succeeded in reducing the disparity levels among regions and provinces in Indonesia.